Community Economic Development for Public Space in Bungwai Sub-District, Warin Chamrab District, Ubon Ratchathani Province - Chaikhan, Sitthichai; Junsiri, Supanee; Makdee, Wanwisa; Odton, Anyani (Area Based Development Research Journal, 2022)
The development of the community economy in the public space of Bung Wai sub-district, Warin Chamrab district, Ubon Ratchathani province aims to increase the average monthly income for people with incomes below the median income of the Thai population by allocating public spaces to create a community market using a participatory process. The processes include the following steps: 1) Creating an understanding of problems, 2) Identifying or specifying problems, 3) Co-designing the community market, 4) Co-constructing the community market, 5) Determining regulations and operations of the community market, 6) Developing the potential of product vendors, and 7) Establishing a community market. The results reveal that the community is able to set up the community market “Nong Hor” at Nong Hor Health Park. The community has allocated 22 sales booths (1 village per booth) for product vendors, namely 20 village members in Bung Wai Sub-District and two volunteer groups from two sub-district health promotion hospitals. The products sold at the market include health products made from local herbs, handicraft products, local agricultural and food products, and souvenirs of the community market. In the experimental operations between June and July 2021, the income of six people below the median income of the Thai population increased by 2,686-3,346 baht per month. The experimental group understood the concept of cost calculation, accounting for income and expenses, sanitary management, and experiences of being the seller of their products. In conclusion, the community used more public spaces, and Bung Wai Sub-District Administrative Organization has requested permission from the treasury office of Ubon Ratchathani Province for the right to manage this area.